2003
DOI: 10.1126/science.1080376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Testicular Odorant Receptor Mediating Human Sperm Chemotaxis

Abstract: Although it has been known for some time that olfactory receptors (ORs) reside in spermatozoa, the function of these ORs is unknown. Here, we identified, cloned, and functionally expressed a previously undescribed human testicular OR, hOR17-4. With the use of ratiofluorometric imaging, Ca2+ signals were induced by a small subset of applied chemical stimuli, establishing the molecular receptive fields for the recombinantly expressed receptor in human embryonic kidney (HEK) 293 cells and the native receptor in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
611
1
19

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(649 citation statements)
references
References 19 publications
18
611
1
19
Order By: Relevance
“…In the human,16, 21, 22, 23 rabbit,10 and mouse,15 sperm chemotaxis to the follicular fluid and egg‐related material has been observed, but the mechanism of sperm chemotaxis is not sufficiently understood. In this study, it was investigated whether bull sperm can be attracted to the BFF.…”
Section: Discussionmentioning
confidence: 99%
“…In the human,16, 21, 22, 23 rabbit,10 and mouse,15 sperm chemotaxis to the follicular fluid and egg‐related material has been observed, but the mechanism of sperm chemotaxis is not sufficiently understood. In this study, it was investigated whether bull sperm can be attracted to the BFF.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs voies de signalisation ont été décrites comme participant au chimiotactisme du spermatozoïde chez les mammifères. La présence de récepteurs olfactifs sur le spermatozoïde a été démontrée et leur activation par des molécules odorantes comme le « bourgeonal » est capable de modifier la trajectoire des spermatozoïdes [14]. La voie de signalisation en aval du récepteur active classiquement une protéine G, puis l'adényl-cyclase de l'ordre de 100 pM, le maximum de potentialisation étant atteint pour des concentrations de l'ordre 100 nM.…”
Section: Des Résultats Actuels Rassurantsunclassified
“…2009) and the chemotaxis of sperm (Spehr et al . 2003), and we have recently shown that olfactory receptors are expressed in the kidney. One of the novel renal G‐protein‐coupled receptors we are interested in is olfactory receptor 78 (Olfr78; Pluznick et al .…”
Section: Introductionmentioning
confidence: 98%